2019
DOI: 10.1103/physrevb.99.081101
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy of the alkali iridate Na2IrO3 at high magnetic fields: Evidence for strong ferromagnetic Kitaev correlations

Abstract: The magnetic field response of the Mott-insulating honeycomb iridate Na2IrO3 is investigated using torque magnetometry measurements in magnetic fields up to 60 tesla. A peak-dip structure is observed in the torque response at magnetic fields corresponding to an energy scale close to the zigzag ordering (≈ 15K) temperature. Using exact diagonalization calculations, we show that such a distinctive signature in the torque response constrains the effective spin models for these classes of Kitaev materials to ones … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…First-principles calculations [4] have found that under high pressure, Na 2 IrO 3 goes through successive structural and magnetic phase transitions, some of them zigzag magnetic ordered and some nonmagnetic, all with low energy excitations that can be well described by j eff = 1/2 states and in particular having some phases (with a structure corresponding to space group P1) [4] resembling a gapped spin liquid Kitaev state. Similarly, magnetic torque measurements have found that at magnetic fields up to 60 T, long-range spin correlation functions decay rapidly pointing to a field-induced quantum spin liquid [6]. In the absence of high pressure or magnetic fields, recent inelastic x-ray scattering measurements have reported a proximate spin liquid regime above the long-range ordering temperature, where fractional excitations are emer-gent, revealed by spin-spin correlations restricted to nearest neighbor sites, among other factors [7].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…First-principles calculations [4] have found that under high pressure, Na 2 IrO 3 goes through successive structural and magnetic phase transitions, some of them zigzag magnetic ordered and some nonmagnetic, all with low energy excitations that can be well described by j eff = 1/2 states and in particular having some phases (with a structure corresponding to space group P1) [4] resembling a gapped spin liquid Kitaev state. Similarly, magnetic torque measurements have found that at magnetic fields up to 60 T, long-range spin correlation functions decay rapidly pointing to a field-induced quantum spin liquid [6]. In the absence of high pressure or magnetic fields, recent inelastic x-ray scattering measurements have reported a proximate spin liquid regime above the long-range ordering temperature, where fractional excitations are emer-gent, revealed by spin-spin correlations restricted to nearest neighbor sites, among other factors [7].…”
Section: Introductionmentioning
confidence: 90%
“…In real materials such as Na 2 IrO 3 , the existence of Heisenberg and off diagonal interactions benefit the appearance of magnetically ordered ground states over a spin liquid. Recent studies have explored the effect of external pressure and high magnetic fields on the ground states of Na 2 IrO 3 [4][5][6]. First-principles calculations [4] have found that under high pressure, Na 2 IrO 3 goes through successive structural and magnetic phase transitions, some of them zigzag magnetic ordered and some nonmagnetic, all with low energy excitations that can be well described by j eff = 1/2 states and in particular having some phases (with a structure corresponding to space group P1) [4] resembling a gapped spin liquid Kitaev state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of these materials exhibit complex long-range magnetic orders at sufficiently low temperatures, indicating that other subdominant interactions between magnetic moments are present and may also have nontrivial bond-dependent character. Both experiment [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and theory [27][28][29][30][31][32][33] have shown that these orders are fragile and can be efficiently suppressed by external magnetic field. It was also found that the competition between the external field and anisotropic bond-dependent exchange interactions gives rise to highly anisotropic magnetization processes and a variety of complex orders at intermediate fields [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the anisotropic exchange couplings could appear in the temperature dependence of the thermodynamic quantities such as the specific heat, spin susceptibility [17] and magnetotropic coefficients [18,19]. Especially for the spin susceptibility and magnetic torque, magnetic fields along different directions induce magnetization of different magnitudes, leading to the anisotropic spin susceptibility [20][21][22][23][24][25] and the angular dependence of the magnetic torque [26][27][28][29], and providing a natural detection of the intrinsic spin anisotropy in the system. To go beyond the thermody-namic properties, we further consider the electron spin resonance (ESR) measurement [30,31] of the system.…”
Section: Introductionmentioning
confidence: 99%